Research on heat dissipation of car seat optimizing based on ARIZ analysis. (August 2019) - Liu, Chunmeng; Dong, Juan; Yang, Xin; Xue, Bingyang; Wu, Fei; Shi, Fu
Abstract: The heat dissipation of car seat back is poor if there is no extra ventilation system. This paper applied ARIZ (Algorithm of Inventive Problem Solving) to get 6 proposals to optimize the heat dissipation of car seat back. Various TRIZ (Theory of Inventive Problem Solving) methods were used, such as Function Model, Cause and Effect Chain, Contradiction Analysis, Substance Field and SLP (smart little people) and so on. All these methods were used by a logical structured process (ARIZ) which incrementally evolves the complex problem to a point where it was simple to solve.